2015
DOI: 10.1002/pc.23685
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of surface‐modified ultra‐high molecular weight polyethylene fiber reinforced natural rubber composites

Abstract: The mechanical properties of ultra‐high molecular weight polyethylene (UHMWPE) fibers reinforced natural rubber (NR) composites were determined, and the effects of fiber surface treatment and fiber mass fraction on the mechanical properties of the composites were investigated. Chromic acid was used to modify the UHMWPE fibers, and the results showed that the surface roughness and the oxygen‐containing groups on the surface of the fibers could be effectively increased. The NR matrix composites were prepared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…Initially, in composites, the minute weight loss (2-3%) start with the loss of bound moisture content and volatilization (un-reacted epoxy/hardener compounds, bound gases, and monomers, etc.) from the matrix at the temperature range from 50˚ to 380 ˚C through dehydration process 21,67 . It is observed that almost every composite had the same degradation curve up to 380 ˚C with almost no weight loss (%).…”
Section: Thermo-gravimetric Test Results and Analysis (Tga)mentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, in composites, the minute weight loss (2-3%) start with the loss of bound moisture content and volatilization (un-reacted epoxy/hardener compounds, bound gases, and monomers, etc.) from the matrix at the temperature range from 50˚ to 380 ˚C through dehydration process 21,67 . It is observed that almost every composite had the same degradation curve up to 380 ˚C with almost no weight loss (%).…”
Section: Thermo-gravimetric Test Results and Analysis (Tga)mentioning
confidence: 99%
“…The loading content of nanofillers considered as an important factor for composites fabrication 19 . The specific weight fraction of nanofiller content mainly depends on the type of composite material, filler size, and resin content [20][21][22] . Research works found out that, as a weight fraction of nanofiller content increases in the matrix beyond specific weight fraction level (wt%), there is a sharp decline in mechanical properties of composites, this is due to the formation of irregular clusters which results in uneven distribution of stresses in the matrix 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…11 illustrated the FTIR spectra of as received and chromic acid-modified UHMWPE. The absorption peaks of 2914, 2847, 1471, and 717 cm -1 were attributed to methylene -CH2 asymmetrical stretch vibration, -CH2 symmetrical stretch vibration, -CH2 non-symmetry changing angle vibration, and -(CH2)n swing in-plane vibration, respectively [37], [38]. The broadband around 3400 cm -1 observed the presence of the hydroxyl group -OH in the spectra of UHMWPE hybrid.…”
Section: Ftir Spectroscopymentioning
confidence: 94%
“…The authors reported that the improvement in flexural strength was due to the addition of nanoparticles. Li et al [ 21 ] fabricated UHMWPE fiber reinforced natural rubber composites and determined its mechanical properties. Researchers reported UHMWPE/rubber hybridization improved the tear strength, break strength, and hardness of the composite.…”
Section: Introductionmentioning
confidence: 99%